2021
DOI: 10.1007/s12291-021-01008-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of P-SEP, sTREM-1 and suPAR as Novel Sepsis Biomarkers in SARS-CoV-2 Infection

Abstract: The coronavirus disease 2019 is a highly contagious viral infection caused by SARS-CoV-2 virus, member of coronaviridae family. It causes life threatening complications due to complexity and rapid onset course of the disease. Early identification of high-risk patients who require close monitoring and aggressive treatment remains challengeable till date. Novel biomarkers which help to identify high risk patients at the early stage is high priority. Objective of this review to find utility of P-SEP, sTREM-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In previous studies, suPAR was mainly used as a biomarker of kidney injury and inflammation, 40 and more recently, as a biological indicator to predict disease severity or poor prognosis in COVID-19 patients. [41][42][43] The soluble receptor for advanced glycation endproducts (sRAGE) is a well-characterized marker of lung alveolar epithelial injury, and its importance in ARDS patients has been proven to correlate with prognostic and pathogenic values. 49,50 The sRAGE can directly or indirectly combine with different types of ligands and stimulate RAGE-associated inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, suPAR was mainly used as a biomarker of kidney injury and inflammation, 40 and more recently, as a biological indicator to predict disease severity or poor prognosis in COVID-19 patients. [41][42][43] The soluble receptor for advanced glycation endproducts (sRAGE) is a well-characterized marker of lung alveolar epithelial injury, and its importance in ARDS patients has been proven to correlate with prognostic and pathogenic values. 49,50 The sRAGE can directly or indirectly combine with different types of ligands and stimulate RAGE-associated inflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, suPAR was mainly used as a biomarker of kidney injury and inflammation, 40 and more recently, as a biological indicator to predict disease severity or poor prognosis in COVID-19 patients. 4143 Alfano et al explained the association of suPAR with viral pathogenesis mechanisms, including the involvement of suPAR in S protein cleavage, and fibrinolytic balance. 9,44 Rovina et al noted that suPAR is an early predictor of the development of severe respiratory failure (SRF) 45 and that higher plasma suPAR levels predict the risk of kidney disease in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sTREM-1 levels are associated with poor clinical outcome in patients with COVID-19, as shown in various studies and a meta-analysis. It is therefore a good candidate as triage tool [ 4 6 , 11 13 ]. IL-6 plays a role in the genesis of the pro-inflammatory lung-systemic loop leading to a cytokine storm syndrome and acute respiratory distress syndrome [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that all those patients who died had progressed to severe COVID and developed ARDS. Chen D et al, 2019 observed serum suPAR levels predicted increased risk of ARDS in patients with sepsis [21]. Furthermore, its upregulation was observed to be directly proportionate with higher disease severity, inflammation and increased mortality in patients with sepsis and ARDS [22].…”
Section: Discussionmentioning
confidence: 99%